Veterinary microbiology and microbial disease - Quinn, P. J. (Wiley-Blackwell, 2011)
"Veterinary Microbiology is one of the core subjects for veterinary students. Fully revised and expanded, this new edition covers every aspect of veterinary microbiology for students in both paraclinical and clinical years. It provides concise descriptions of the groups of micro-organisms, diseases they produce, immunological aspects and a summary of infectious diseases based on their main clinical signs. New to this edition:Diagrams throughout showing the transmission of infection New chapters on the application of molecular methods, food safety and public health, skin, the respiratory system, cardiology, and the urinary tract Revisions to existing text and many more illustrations"--Provided by publisher.